(untitled) (Communication & Society, 2023)
Television series act as one of the primary sources of information on mental and neurological disorders. However, research on the accurate representation of mental disorders and clinical reality still lacks, especially since it requires an interdisciplinary approach with higher complexity. This article analyses the narrative depiction of depression, autism without intellectual disability, and antisocial personality disorder in three case studies: Atypical (Netflix, 2017-present), My Mad Fat Diary (E4, 2013-2015), and The End of The F***ing World (E4 & Netflix, 2017-2019). The aim is to identify which stereotypes are still predominant on-screen and determine whether they are reliable with their clinical reality. Hence, the authors propose a narrative content analysis based on the medication, symptoms, diagnosis, and treatment according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) and Stahl’s Essential Pharmacology Guide. The authors applied a methodology based on the standard analysis measurement of different case studies under a unified pattern for mental disorders’ intrinsic socio-economic and gender aspects. The results showed that TV series try to opt for better representations, but many still perpetuate misconceptions and misrepresentations due to a tension between showing realistic, educational values (edutainment) and opting for a gripping audio-visual and narrative drama. In conclusion, diverse realities are hardly achieved. Moreover, TV series criticise how the anger is placed on oneself instead of the system.